IMPLEMETATION OF MODEL SAVI (SOMATIC, AUDIOTORY, VISUALIZATION, INTELLECTUAL) TO INCREASE CRITICAL THINKING ABILITY IN CLASS IV OF SOCIAL SCIENCE LEARNING ON SOCIAL ISSUES IN THE LOCAL ENVIRONMENT - Dadang Iskandar; Acep Roni Hamdani; Teti Suhartini (JETL (Journal of Education, Teaching and Learning), 2016)
This research is motivated by the lack of critical thinking skills of fourth grade students of SDN Tanjung III, Subang district. On the basis of the need for repairs done either by applying the model of SAVI (Somatic, Auditory, Visualization, Intellectual). So the purpose of this study was to determine the increase critical thinking skills of students in Social Science before and after applying the model SAVI, the performance of teachers in applying the model SAVI, activities and students' response to the model SAVI. The method used in this research is the CAR (Classroom Action Research). Subject of research that fourth grade students of SDN Tanjung III by the number of students as many as 23 people. The instrument used was LKS (Student Worksheet), observation sheet of students and teachers as well as student questionnaire responses. From these results, it can be concluded that by applying the model in study SAVI social science with social problems in the local environment can enhance students' critical thinking skills. The result can be seen from the percentage of the overall level of mastery learning increased from 52.2% in the first cycle, 78.3% in the second cycle and 100% in the third cycle. The average grade class of students increased from 44.3 prasiklus of data with less criteria, up to the third cycle, which reached 91.3 with the criteria very well. With the improvement of students' critical thinking skills that are calculated based on the n-gain of 0.53 with the criteria of being in the first cycle, and 0.65 with the criteria of being on the second cycle, and 0.81 with the high criteria of the third cycle. The results of observations also showed that the ability of teachers and students' activity in applying the model of SAVI increased. Based on questionnaire responses, 100% of students showed interest in learning social science model with SAVI. Therefore, it is suggested that teachers use models SAVI  to enhance the critical thinking skills of students so that students used to learn to analyze problems well.